Le Street Art aux Petites Antilles Françaises - Anne-Catherine Berry (Cahiers de Narratologie)
This paper examines artistic practises in the urban public space of the French Antilles, especially in Martinique and Guadeloupe. Since the end of the 1980, this art form has appeared on the street walls of both islands and has progressively spread. Tags and graffitis – which seemed rather punctual and isolated incidents-appeared first, later followed by murals, collages or even installations. Although some of these practises are still occasional, their presence in the urban landscape creates a real impact, be it a visual, aesthetic or semantic one. Most importantly, they seem to tell about the special features of the islands. Whether the artists are self-taught or professionally trained, they testify to their particular regional context whose complexity comes from its plurality. Some are truly artistically engaged, showing their belief in the concept of a West Indian identity. Such contributions tend to reveal how deeply rooted in the idea of a plural society this type of art is. As a blending of different ethnies, the Creole culture creates the environment where artworks can emerge and shares a special link with them. How can these works testify to the singularities of this culture ? What do they tell about it and what feelings can they arouse ?